Highly sensitive imaging of renal microcirculation in vivo using ultrahigh sensitive optical microangiography - Zhi, Zhongwei (Optical Society of America, 2011)
Studying renal microcirculation and its dynamics is of great importance for understanding the renal function and further aiding the diagnosis, prevention and treatment of renal pathologies. In this paper, we present a potentially useful method to provide high-sensitive volumetric imaging of renal microcirculations using ultrahigh-sensitive optical microangiography (UHS-OMAG). The UHS-OMAG image system used here is based on spectral domain optical coherence tomography, which uses a broadband light source centered at 1300 nm with an imaging speed of 150 frames per second that requires ~6.7 sec to complete one 3D scan of ~2.5 × 2.5 mm(2) area. The technique is sensitive enough to image capillary networks, such as peritubular capillaries within renal cortex. We show the ability of UHS-OMAG to provide depth-resolved volumetric images of capillary level renal microcirculation. We also show that UHS-OMAG is capable of monitoring the changes of renal microcirculation in response to renal ischemia and reperfusion. Finally, we attempt to show the capability of OMAG to provide quantitative analysis about velocity changes in a single capillary vessel (down to tens of microns per second) in response to the ischemic event.